ANALISIS PENGARUH LINGKUNGAN KERJA NON FISIK DAN MUTU INFORMASI TERHADAP PRODUKTIVITAS KARYAWAN DENGAN PERILAKU ADAPTIF SEBAGAI VARIABEL INTERVENING - Alfatha, Muhammad Yusuf; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2018)
Companies nowadays prioritizes employee’s experience in work. This is shown from the employee's productivity that is influenced by the non-physical work environment and the quality of information within the company. Employee productivity is also influenced by the ability to adapt to its work. This study examines the influence of Non Physical Work Environment and the quality of information on employee productivity with adaptive behavior as intervening variable. The method used in this study is to use multiple linear regression to test the direct hypothesis and path analysis to test the indirect influence of the hypothesis tested.The results of this research indicate a significant positive influence between non-physical work environment with adaptive behavior, quality of information with adaptive behavior, adaptive behavior with employee productivity and non-physical work environment with employee productivity, while the quality of information with employee productivity has positive but not significant influence. In conclusion, this research is able to prove the proposed hypothesis.